Effects of bariatric surgery upon the sympathetic nervous system and hypothalamic-pituitary-adrenal axis in obese humans - Andreas Kraag Ziegler; Mette Christensen; Henrik Løvendahl Jørgensen; Mogens Fenger; Sara Fogh Myrup; Carsten Dirksen; Sten Madsbad (Scientific Reports)
Abstract Human obesity is a state of hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis and dysfunction of the sympathetic nervous system (SNS). It is unclear whether weight loss will normalize this apparent dysfunction and if potential changes are of short -or long-term duration. In this study, we test how weight reduction following Roux-en-Y Gastric Bypass (RYGB) surgery affects the HPA-axis and SNS activity for a follow-up period of 2 years. We show that a ≈ 30% reduction in bodyweight following RYGB, is accompanied by an increase in circulating cortisol, and decrease in the concentrations of systemic metanephrines concomitant with a transient reduction in systolic blood pressure, and that the endocrine changes persist for at least 24 months post-surgery. The decrease in SNS activity was weakly, but significantly correlated with postoperative improvements in HbA1c. These findings suggests that the anatomical rearrangement of the gastrointestinal system by bariatric surgery, and the resulting marked decrease in body weight, have long-term impact on the autonomic nervous system. The biological significance of these findings is uncertain though it could be speculated that chronically elevated serum cortisol, may be involved in the development of osteoporosis, a well-known risk of bariatric surgery, as well as control of glucose and lipid metabolism. Furthermore, the chronic reduction in metanephrines observed, suggest that SNS depression may contribute to both a reduction in blood pressure and better glycemic control following surgery. We collectively demonstrate that RYGB surgery has an early and persisting impact on the HPA-axis and the sympathetic nervous system, and that this is associated with bodyweight reduction and improved glycemic control.